(untitled) (Journal of history, 2021)
The publication can be attributed to the edu- cational literature on the archeology of Kazakh- stan. During the time of independent Kazakhstan, the first book of Baypakov K.M., Taimagambetov Zh.K., Zhumaganbetov T.S. was published in 1993. With the accumulation of archaeological materi- als, new scientific hypotheses and ideas, Professor Baypakov K.M. and Taimagambetov Zh.K. wrote and published in Russian and Kazakh languages a completely new book “Archeology of Kazakhstan” in 2007. (Baypakov K.M., Taimagambetov Zh.K. Archeology of Kazakhstan. – Nur-Sultan, “Eur- asian University named after L.N. Gumilyov”, 2021. – 622 pages (in English). To this day it re- mains the only one, no such literature has been pub- lished before.